Development of nonlinear 3-D, and novel 2-D optical microscope imaging systems for time-lapse imaging - Girardin, Robert Joseph (My University, 2004)
The design and development of a nonlinear two-photon, 3-D microscope imaging system, software for manipulation of 2-D and 3-D images, and the operation of a novel 2-D imaging system used for monitoring cultured live cell activity for many hours, is reported. Included in the first portion of the thesis is the description of the final assembly of a mode-locked Ti:Sapphire laser producing 10 - 100 femtosecond pulses at high repetition rate. Also described is the construction and computer automation of a laser microscope with digitally controlled XY mirror laser beam scanning and with linear motor stage Z-stepping. This system was later used to image GFP tagged cultured live cancer cells. As a companion instrument and 2-D reference system for comparative time-lapse imaging studies of cancer cells, a Nikon E400 fluorescence microscope and cooled CCD detector were purchased and integrated. Central objectives of the live cell studies were (a) to find a method of readily imaging untagged cells which can be cultured from needle biopsies taken from patients, and (b) to develop a method for semi-quantitatively ascertaining live cell vitality over time frames extending from minutes to hours. The short time scale is particularly useful as it provides information that cannot be obtained from monitoring the cell division process, which is measured in many hours. The ability to monitor cell viability is important when monitoring the effects of external treatments such as radiation, intense light, chemicals, or any combination of these. The Nikon fluorescence microscope permitted automated collection of incubated, untagged live cell image data for many hours time duration via a technique called ‘oblique illumination microscopy’ (OIM), also referred to as ‘oblique incidence reflection imaging’. Untagged cells are very difficult samples to see by means of commonly used imaging methods such as transmitted, fluorescence, or epi-reflection illumination methods. The ability of OIM to avoid the necessity of fluorescence tagging of the cell samples, its use of very low intensity illumination and hence low optical toxicity, made it the central technique used for many of the live cell time-lapse studies carried out in this work and presented as part of this thesis.
Keywords: Chronophotography; Cancer Photochemotherapy Research; Confocal microscopy